Gambaran Pedagogical Content Knowledge (PCK) pada Calon Guru Biologi Di Universitas Kristen Indonesia - Riska Septia Wahyuningtyas; Janed Lauren Soplantila; Jendri Mamangkey (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research aimed to determine the ability level of Pedagogical Content Knowledge (PCK) students of biology education at the Christian University of Indonesia. This research was a qualitative descriptive research. Data collection was carried out in two ways, namely by conducting a survey of respondents about pedagogic knowledge and content knowledge, then observing the learning implementation plan document which was assessed by two panelists. The population in this study were students of the Biology Education study program at the Christian University of Indonesia. The conclusion of this study was 1) The level of Pedagogical Content Knowledge (PCK) ability of biology education students was sufficient in terms of the results of written tests regarding Pedagogical Content Knowledge (PCK) knowledge, 2) Biology education students' Pedagogical Content Knowledge (PCK) ability level entry into the criteria is sufficient in terms of the results of the observation of the learning implementation plan (RPP) document